Penerapan Strategi Digital Marketing dalam Meningkatkan Penghimpunan Dana ZIS (Zakat, Infaq, dan Shodaqoh) di Laznas IZI Jawa Timur - Amrina, Mila; Fahrullah, Arasy (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of the research is for having a knowledge about the implementation of digital marketing strategy used to gain more collections of ZIS in Amil Zakat National Institution of IZI East Java, and also to knowing the Islamic economics perspective of those digital marketing strategy they used. This research uses descriptive qualitative methods with having an observation, interview and documentation. The result shows that IZI East Java is using digital marketing strategy through their social media such as Whatsapp, instagram, facebook ads, youtube, e-mail and zakatpedia platform with preparing the strategy of segmentation, targeting, positioning, differentiation, marketing mix, selling, brand, service and process in their marketing. But, the digital marketing by whatsapp selling brings the impact on ZIS collections improvement in IZI East Java. The digital marketing used by IZI East Java is already in the way how syariah marketing should be, and it runs well because of the modern technology, but it has some problem such as maintenance issues on zakatpedia platform.